Revision of the Metallactus taeniatellus species group (Coleoptera: Chrysomelidae: Cryptocephalinae) - Sassi, Davide (Zootaxa, 2022)
The taeniatellus species group of Neotropical Metallactus Suffrian, 1866 of the subtribe Pachybrachina is defined and 10 species are revised and assigned to the group. Four of them already belonged to Metallactus. They are: Metallactus taeniatellus, Suffrian, 1866, M. insitivus, Suffrian, 1866, M. latiusculus, Suffrian, 1866, M. planipennis, Suffrian, 1866. Four additional species, formerly included in Griburius Haldemann, 1849 (= Scolochrus, Suffrian, 1852), are transferred to Metallactus and assigned to the M. taeniatellus species group: Metallactus cultus (Suffrian, 1866) comb. nov., M. quadrinus (Suffrian, 1866) comb. nov., M. superbiens (Suffrian, 1866) comb. nov. and M. multicolor (Jacoby, 1899) comb. nov. Two additional species are described as new to science: Metallactus geiseri sp. nov. and M. uncinatus sp. nov. Lectotypes are designated for Metallactus cultus, M. insitivus, M. latiusculus, M. multicolor, M. planipennis, M. quadrinus, M. superbiens, and M. taeniatellus. Description, figures, and range maps are given for each species. An identification key for the species in the taeniatellus species group is also provided.